Purinergic receptors are part of a signalling system for proliferation and differentiation in distinct cell lineages in human anagen hair follicles - Greig, Aina V. H. (Springer Netherlands, 2008)
We investigated the expression of P2X(5), P2X(7), P2Y(1) and P2Y(2) receptor subtypes in adult human anagen hair follicles and in relation to markers of proliferation [proliferating cell nuclear antigen (PCNA) and Ki-67], keratinocyte differentiation (involucrin) and apoptosis (anticaspase-3). Using immunohistochemistry, we showed that P2X(5), P2Y(1) and P2Y(2) receptors were expressed in spatially distinct zones of the anagen hair follicle: P2Y(1) receptors in the outer root sheath and bulb, P2X(5) receptors in the inner and outer root sheaths and medulla and P2Y(2) receptors in living cells at the edge of the cortex/medulla. P2X(7) receptors were not expressed. Colocalisation experiments suggested different functional roles for these receptors: P2Y(1) receptors were associated with bulb and outer root sheath keratinocyte proliferation, P2X(5) receptors were associated with differentiation of cells of the medulla and inner root sheaths and P2Y(2) receptors were associated with early differentiated cells in the cortex/medulla that contribute to the formation of the hair shaft. The therapeutic potential of purinergic agonists and antagonists for controlling hair growth is discussed.